Emotion‐focused therapy for binge‐eating disorder: A review of six cases - Glisenti, Kevin; Strodl, Esben; King, Robert (Clinical psychology and psychotherapy, 2018)
Objective This study aimed to provide preliminary evidence of the usefulness of emotion‐focused therapy (EFT) for binge‐eating disorder (BED). Methods We used a single‐subject design in which 12 weeks of individual EFT were applied nonconcurrently to six female adult participants with BED, following three weekly baseline sessions. Participants were assessed for binge‐eating psychopathology and emotion regulation difficulties on a weekly basis during baseline and treatment. They were assessed on a 2‐, 4‐, and 8‐week basis during posttreatment, and they were assessed for binge‐eating episodes, eating disorder attitudes, alexithymia, and psychiatric comorbidity at pretreatment and posttreatment. Results All cases experienced reliable recovery from binge‐eating psychopathology and a significant decrease in binge‐eating frequency. For all cases, there was reliable improvement or recovery on eating and shape concerns, and there was improvement on weight concern for the majority of cases. For all cases, reliable recovery or improvement occurred in overall emotion regulation. Most cases that were in the clinical range pretreatment recovered for anxiety, and reliable improvement in or recovery from depression occurred for all cases. There was reliable recovery or improvement in alexithymia for half of the cases; however, the other half experienced no change or deteriorated. There were no treatment dropouts. Conclusion Individual EFT demonstrates potential as a psychological treatment for BED. The current study provides preliminary evidence to guide the development of a more extensive trial to test the efficacy of individual EFT for BED as well as to identify possible mechanisms of change.